Onset of opportunity to use cannabis and progression from opportunity to dependence: Are influences consistent across transitions?. (1st March 2016) - Hines, Lindsey A.; Morley, Katherine I.; Strang, John; Agrawal, Arpana; Nelson, Elliot C.; Statham, Dixie; Martin, Nicholas G.; Lynskey, Michael T.
Highlights: The development of dependence is a multi-stage process. Risk factors may be stage specific. We focus on speed of transition to opportunity to use cannabis, and to dependence. The two transitions had a unique profile of risk factors. Evidence of stage-specific risk factors highlights intervention opportunities. Abstract: Background: There is a developing body of research looking at cannabis use opportunity, but little research examining timing of opportunity to use cannabis. Aims: Identify factors associated with (1) earlier opportunity to use cannabis and (2) faster progression from opportunity to cannabis dependence. Method: Cross-sectional study of 3824 Australian twins and siblings, measuring age of onset of cannabis use opportunity and DSM-IV cannabis dependence. Survival analysis identified factors associated with faster progression to opportunity or dependence. Results: Factors associated with both speed of progression to opportunity and dependence were conduct disorder (opportunity HR 5.57, 95%CI 1.52–20.47; dependence HR 2.49, 95%CI 1.91–3.25), parental drug problems (opportunity HR 7.29, 95%CI 1.74–30.62; dependence HR 3.30, 95%CI 1.63–6.69), weekly tobacco use (opportunity HR 8.57, 95%CI 3.93–18.68; dependence HR 2.76, 95% CI 2.10–3.64), and female gender (opportunity HR 0.69, 95%CI 0.64–0.75; dependence HR 0.44, 95%CI 0.34–0.55). Frequent childhood religious attendance (HR 0.74, 95%CI 0.68–0.80), parental conflict (HR 1.09, 95%CI 1.00–1.18), parental alcohol problems (HR 1.19, 95%CI 1.08–1.30) and childhood sexual abuse (HR 1.17, 95%CI 1.01–1.34) were uniquely associated with transition to opportunity. Depressive episode (HR 1.44, 95%CI 1.12–1.85), tobacco dependence (HR 1.36, 95%CI 1.04–1.78), alcohol dependence (HR 2.64, 95%CI 1.53–4.58), other drug use (HR 2.10, 95%CI 1.64–2.69) and other drug dependence (HR 2.75, 95%CI 1.70–4.43) were uniquely associated with progression to dependence. Conclusion: The profile of factors associated with opportunity to use cannabis and dependence only partially overlaps, suggesting targeting of interventions may benefit from being tailored to the stages of drug use.